2018
DOI: 10.1002/jso.25280
|View full text |Cite
|
Sign up to set email alerts
|

A 96‐hour continuous wound infiltration with ropivacaine reduces analgesic consumption after liver resection: A randomized, double‐blind, controlled trial

Abstract: Background: Continuous wound infiltration (CWI) with local anesthetics to reduce morphine consumption in postoperative pain management after open liver resection in patients with cancer.Methods: This single-center randomized double-blind study allocated patients requiring resection of liver metastases to receive a 3.75 mg/mL ropivacaine (ROP) infiltration, followed by a 2 mg/mL ROP CWI, or placebo (P) for 96 hours.Postoperative analgesia included acetaminophen and patient-controlled analgesia morphine pump. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Compared to placebo, both continuous and single-shot ropivacaine WI resulted in lower pain scores, reduced opioid consumption, reduced stress hormones levels, shorter LOS, and faster bowel recovery after open hepatectomy [158][159][160]. CWI showed equivalent efficacy as epidural PCA and opioid intravenous analgesia after open hepatectomy [161,162].…”
Section: Hepatic Biliary and Pancreatic Surgerymentioning
confidence: 94%
“…Compared to placebo, both continuous and single-shot ropivacaine WI resulted in lower pain scores, reduced opioid consumption, reduced stress hormones levels, shorter LOS, and faster bowel recovery after open hepatectomy [158][159][160]. CWI showed equivalent efficacy as epidural PCA and opioid intravenous analgesia after open hepatectomy [161,162].…”
Section: Hepatic Biliary and Pancreatic Surgerymentioning
confidence: 94%
“…5 Wound infiltration with local anesthetics is a very simple and effective local analgesic technique. 7,8 As a previous randomised trial reported, wound infiltration with ropivacaine could significantly reduce postoperative pain and postoperative analgesic consumptions in thoracotomy. 9 To the authors' best knowledge, until now, no randomised, controlled, clinical study has been conducted to compare the effects of preoperative ultrasound-guided ESPB and wound infiltration with local anesthetics on perioperative opioid consumption and postoperative pain in thoracotomy.…”
Section: Introductionmentioning
confidence: 93%
“…Another similar study found that local anesthetic infusion through a subfascial catheter reduced opioid use but did not influence pain scores. 26 Basic analgesia consisted of acetaminophen and nefopam. 26 Yet another placebo-controlled RCT reported that local anesthetic infusion through two catheters placed-one in the subfascial plane and the other subcutaneously-resulted in significantly lower pain scores at rest at 8 and 16 hours but no difference on pain associated with movement.…”
Section: Reviewmentioning
confidence: 99%
“…26 Basic analgesia consisted of acetaminophen and nefopam. 26 Yet another placebo-controlled RCT reported that local anesthetic infusion through two catheters placed-one in the subfascial plane and the other subcutaneously-resulted in significantly lower pain scores at rest at 8 and 16 hours but no difference on pain associated with movement. 27 The use of basic analgesics was not reported.…”
Section: Reviewmentioning
confidence: 99%